2023
DOI: 10.1039/d2ta08366c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Ni2P/Zn–Ni–P nanosheet array for efficient energy-saving hydrogen evolution and hydrazine oxidation

Abstract: Electrochemical overall water splitting (OWS) includes two half reactions of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Due to the limitation of the slow kinetic process of OER,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…The nitrides, , sulfides, , phosphides, ,,,, and selenides ,, of Ni and Co are popular HzOR electrocatalysts. E onset values as low as −0.18 to 0 V vs RHE at pH = 14 were reported for such inorganic phases, ,,, including on carbon ,,,, or metallic foam supports. ,,, ,,, Nanoparticles of FeP, Cu 3 P, Cu 2 Se, and RuP 2 are active toward the HzOR, with reported onsets as low as −0.1 V vs RHE for the Ru-based material. However, most transition metals (including Ni, Co, Cu, and Fe) are most stable as hydroxides at pH 14 at 25 °C. , Thus, the inorganic compounds serve only as precursors, so that the catalytic hydroxide surface forms in situ .…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The nitrides, , sulfides, , phosphides, ,,,, and selenides ,, of Ni and Co are popular HzOR electrocatalysts. E onset values as low as −0.18 to 0 V vs RHE at pH = 14 were reported for such inorganic phases, ,,, including on carbon ,,,, or metallic foam supports. ,,, ,,, Nanoparticles of FeP, Cu 3 P, Cu 2 Se, and RuP 2 are active toward the HzOR, with reported onsets as low as −0.1 V vs RHE for the Ru-based material. However, most transition metals (including Ni, Co, Cu, and Fe) are most stable as hydroxides at pH 14 at 25 °C. , Thus, the inorganic compounds serve only as precursors, so that the catalytic hydroxide surface forms in situ .…”
Section: Nanoparticlesmentioning
confidence: 99%
“…8f). 110 Though the coupled value-added anodic reaction (UOR and HzOR) with HER which could produce less valuable chemicals, they have the potential to solve the problem of serious environmental pollution and eutrophication of water resources.…”
Section: Pollutant Oxidation Reactionmentioning
confidence: 99%
“…, have been widely developed and have shown promising catalytic activity for the HER or HzOR. 20–24 The inspiring progress in hydrazine-assisted H 2 generation has also been realized by some pioneering works. For instance, Li et al reported a highly efficient bifunctional material (CC@CoNC) for hydrazine-assisted seawater electrolysis, which delivers a small cell voltage of 0.557 V at 200 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a series of non-precious metal electrocatalysts, including metal phosphides, hydroxides, sulfides, etc., have been widely developed and have shown promising catalytic activity for the HER or HzOR. [20][21][22][23][24] The inspiring progress in a School of Chemistry and Chemical Engineering, Key Laboratory of Surface &…”
Section: Introductionmentioning
confidence: 99%